137Caesium, 40K and total K in Boletus edulis at different maturity stages: Effect of braising and estimated radiation dose intake. (April 2021) - Falandysz, Jerzy; Saba, Martyna; Strumińska-Parulska, Dagmara
Abstract: We studied activity concentrations of artificial 137 Cs and natural 4 0 K and concentration of total potassium (K) in Boletus edulis at different maturity stages (button, young – white, large – white and large - yellow), and the effect of braising and human dietary intake. Mushrooms were collected from the northern region of Poland in 2019. The 137 Cs activity concentration was significantly higher in raw and braised button stage samples and decreased as the fruitbody matured, but conversely, 4 0 K was lower in the raw button stage than in older fruitbodies. 137 Cs activity concentrations in raw, button stage B. edulis were 36 ± 1 Bq kg −1 ww (360 ± 1 Bq kg −1 dw), increasing to 70 ± 2 Bq kg −1 ww (290 ± 7 Bq kg −1 dw) when braised. This activity was around fourteen-fold higher ( p  < 0.0001) than at higher maturity stages which showed 2.5 ± 0.7 Bq kg −1 ww (25 ± 7 Bq kg −1 dw) in raw and 4.9 ± 0.7 Bq kg −1 ww (19 ± 4 Bq kg −1 dw) in braised fruitbodies. In comparison to raw B. edulis, braising enriched the activity concentrations of 137 Cs at 110 ± 69% and 4 0 K at 80 ± 56% on a whole (wet) weight basis. Graphical abstract: Image 1 Highlights: 137 Cs contamination in button stage B. Edulis was 14-fold higher than older stages. Young, large (white) and mature (yellow) B. edulis show similar 137 Cs contamination. 4  K in the fruitbody was lower during button stage than at higher maturity. 137 Cs and 4  K (Bq kg −1 ww) in braised B. edulis were double that of the raw product.